Antioxidant Activity of Moringa oleifera and Olive Olea europaea L. Leaf Powders and Extracts on Quality and Oxidation Stability of Chicken Burgers - Marwa Ezz El-Din Ibrahim; Randah Miqbil Alqurashi; Fatimah Yousef Alfaraj (MDPI AG, 2022)
Oxidation is the main cause of quality deterioration in meat-based foods, such as burgers. Antioxidants inhibit the oxidation process; recently, natural antioxidants have gained interest, due to safety concerns. In this study, the effects of leaf powder and crude extracts of both Moringa oleifera and olive in chicken burgers were studied for their antioxidant potential in preventing fat oxidation during storage. Antioxidant activities were evaluated using DPPH (2,2-diphenyl-1-picrylhydrazyl). The results showed the highest DPPH radical scavenging with IC50 values of 2.397 ± 0.10 mg/mL in the Moringa leaf. Total phenolic content (TPC) was crude olive extract > crude Moringa extract > olive leaf > Moringa leaf. The total flavonoid content (TFC) was significantly higher in the olive leaf and its crude extract than in the Moringa leaf and its crude extract. The pH, total volatile nitrogen, and sensory properties were affected by the addition of olive and Moringa (leaf and crude extracts) to chicken burgers refrigerated for 20 days. The addition of Moringa and olive leaf powder decreased lipid oxidation and PV after 10 days of storage. In general, Moringa and olive leaf treatments slowed the deterioration of meat, suggesting their use as preservatives to extend the shelf-life of chicken burgers.